Low-fat Brazilian cooked sausage-Paio - with added oat fiber and inulin as a fat substitute: effect on the technological properties and sensory acceptance - Bis Souza, Camila Vespucio [UNESP]; Bonadio Bellucci, Elisa Rafaela [UNESP]; Manuel Lorenzo, Jose; Silva Barretto, Andrea Carla da [UNESP] (Soc Brasileira Ciencia Tecnologia Alimentos, 2019)
The aim of this study was to optimize the addition of oat fiber and inulin as fat substitutes in cooked Paio sausage using response surface methodology. The chemical composition, textural parameters, color properties, lipid oxidation, microbial analysis and sensory properties were assessed in twelve different treatments. The addition of dietary fiber led to a significant (P < 0.05) increase in moisture content and also a decrease in fat content of between 60.78% and 63.16%. Color parameters were significantly affected by the addition of inulin and oat fiber, as lightness decreases with the addition of oat fiber. Similar happened with redness, the lowest results were for the treatment with higher dietary fiber content added. Regarding lipid oxidation, the inclusion of fiber did not influence the TBARS values among treatments and throughout the storage time. Sausages manufactured with inulin and oat fiber present similar scores for color, taste and overall acceptability, while lower texture values were found in sausages manufactured with oat fiber. The addition of up to 6% of inulin with up to 0.85% oat fiber in a low fat cooked Paio sausage did not compromise technological parameters and sensory acceptably.
Keywords: dietary fibre; meat products; consumer acceptability studies; texture profile analysis; reformulation